2022
DOI: 10.3390/nu14091894
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Amorphous Calcium Carbonate on the Inflammatory and Muscle Damage Response in Experienced Resistance Trained Individuals

Abstract: The effect of 3 weeks of amorphous calcium carbonate (ACC) supplementation (2000 mg per day) was examined on the recovery response to resistance exercise. Thirty men were randomized into a supplement (ACC) or placebo (PL) group. Following supplementation, participants performed six sets of 10 repetitions in the bench press (BP) and incline BP exercises, using 80% of maximal strength. Participants returned 24 (T4) and 48 h (T5) later and performed six sets of the BP exercise. Significant decreases in the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Considering the role of the carbonate component of the ACC, Hoffman et al [ 8 ] concluded that ACC supplementation may have potentially lessened the decline in performance, which is possibly due to the carbonate component of the ACC. Since there are no published studies on the ergogenic effects of ACC, we again examined studies which investigated NaHCO 3 supplementation effects on performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the role of the carbonate component of the ACC, Hoffman et al [ 8 ] concluded that ACC supplementation may have potentially lessened the decline in performance, which is possibly due to the carbonate component of the ACC. Since there are no published studies on the ergogenic effects of ACC, we again examined studies which investigated NaHCO 3 supplementation effects on performance.…”
Section: Discussionmentioning
confidence: 99%
“…A few reviews (i.e., meta-analyses) have concluded that long-term calcium supplementation (over 12 months) is effective in enhancing bone strength; it also has been suggested that this supplementation is more effective when combined with vitamin D [ 6 , 7 ]. Most of the calcium carbonate supplementation studies were carried out on an older population and often combined with vitamin D. Except for Hoffman et al’s [ 8 ] study using amorphous calcium carbonate (ACC) supplementation, there is little research which studies the effectiveness of calcium carbonate supplementation on muscle performance or recovery from exercise in physically active individuals and athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ACC has been identified as a potential strategy for mitigating performance loss and reducing soreness in high-endurance-trained athletes, due to its inherent response to acids 197 . PolyP-stabilized ACC also exhibits the ability to promote the healing of skin lesions 198 ( Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…Combinations act as bioseeds for the deposition of bone minerals and as inducers of CAIX gene expression 179 2. They induce ALP, promoting the release of inorganic phosphate PolyP stabilized ACC The system induced the expression of ALP gene 183 , 186 Calcium supplement ACC capsules containing 192 mg of elemental calcium A higher bioavailability of calcium from ACC compared to crystalline CaCO 3 191 A Tc modified and Sim-loaded PL- ACC hybrid NPs Calcium supplements, in combination with Sim, activate BMP-2 in osteoblasts through the BMP-Smad signaling pathway, thereby promoting the formation of new bone 195 A Tc modified and MS-coated ACC platform loaded with Sim 109 Gene Delivery ACC/Ca(II)-IP6 compound NPs- siRNA complexes Non-viral gene carriers efficiently transfer siRNA to target cells with high transfection efficiency, ensuring the protection of siRNA from degradation 149 Alginate/CaCO 3 nanoparticles with DOX and P53 expression plasmid Ca 2+ forms a co-precipitate with DNA, facilitating the synergistic delivery of genes and drugs 196 Pain Relief ACC supplementation (2000 mg per day) ACC exhibits enhanced buffering capacity, potentially providing faster and more effective H + buffering 197 Wound Healing PolyP-stabilized ACC The migration propensity of endothelial cells is increased 198 TCPP, meso-tetra-(4-carboxyphenyl) porphine; ACC, amorphous calcium carbonate; DOX, doxorubicin; OA, oleic acid; PEG, polyethylene glycol; NPs, nanoparticles; ICG, indocyanine green; IMQ, imiquimod; PL, phospholipid; US, ultrasound; polyp, polyphosphate; CA, carbonic anhydrase; ALP, alkaline phosphatase; Tc, tetracycline; Sim, simvastatin; BMPs, bone morphogenetic proteins. …”
Section: Applicationsmentioning
confidence: 99%